PERBANDINGAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN CRH PADA MATERI HIDROLISIS GARAM - Nadia Amida; Andromeda Andromeda; Bahrizal Bahrizal (University of Bengkulu, 2018)
Lesson about hydrolysis requires students to understand the concepts hydrolyzed from type of salt which is then applied in the calculation. In learning process, students direct involvement is necessary, so that it is used a method that can increase the activity of students. Student Teams Achievement Division (STAD) cooperative learning and Course Review Horey (CRH) expected to create learning that has caharacterized as student centered. This research aims to reveal students' learning outcomes using STAD cooperative learning and CRH on the hydrolisis material in class XI SMAN 8 Padang. This type of research is experimental research using a randomized study design Control Group Posttest-Only Design is expanded. The study population was a class XI IPA SMAN 8 Padang. Giving a test at the end of the study as many as 25 pieces of matter objectively. Results of tests of normality and homogeneity of the two classes that both classes of samples obtained samples were normally distributed and had homogeneous variance. After being tested on a real level t = 0.05 with degrees of freedom (df) of 59 obtained t of 2.53 while t table of 1.67. From the research shows that the learning outcomes of students with STAD cooperative learning model is significantly higher than the results of student learning with cooperative learning model CRH hydrolysis of salts in the material in class XI of SMAN 8 Padang.